2013
DOI: 10.1371/journal.pone.0083493
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Studies Revealed Local Adaptation in a High Gene-Flow Marine Fish, the Small Yellow Croaker (Larimichthys polyactis)

Abstract: The genetic differentiation of many marine fish species is low. Yet local adaptation may be common in marine fish species as the vast and changing marine environment provides more chances for natural selection. Here, we used anonymous as well as known protein gene linked microsatellites and mitochondrial DNA to detect the population structure of the small yellow croaker (Larimichthys polyactis) in the Northwest Pacific marginal seas. Among these loci, we detected at least two microsatellites, anonymous H16 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 84 publications
2
46
1
Order By: Relevance
“…Although neither meta-analysis evaluated the importance of gene flow per se, the absence of any impact of plant life history or mating system on local adaptation suggests that gene flow may not play a particularly strong role. This view is consistent with empirical studies documenting strong local adaptation in the face of significant gene flow [11][12][13][14]. In summary, existing theory focusing on the balance between gene flow and selection does not adequately explain the abundant variation in the magnitude of local adaptation observed across reciprocal transplant studies [9,10].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although neither meta-analysis evaluated the importance of gene flow per se, the absence of any impact of plant life history or mating system on local adaptation suggests that gene flow may not play a particularly strong role. This view is consistent with empirical studies documenting strong local adaptation in the face of significant gene flow [11][12][13][14]. In summary, existing theory focusing on the balance between gene flow and selection does not adequately explain the abundant variation in the magnitude of local adaptation observed across reciprocal transplant studies [9,10].…”
Section: Introductionsupporting
confidence: 75%
“…In addition to explaining variation in levels of local adaptation observed among studies, our results may help explain why strong local adaptation is sometimes observed in organisms with high rates of gene flow [11][12][13][14]. There are two ways in which trait dimensionality facilitates the evolution of strong local adaptation, even in the face of substantial gene flow.…”
Section: (C) Implications For Local Adaptationmentioning
confidence: 87%
“…In certain situations, adaptive differences in the face of high gene flow are the only discriminating factor through which concise fishery management is possible, by disentangling the effects of selection from demographic history, migration and genetic drift [24, 116, 117]. For example, Nayfa and Zenger [32] detected divergent selection between three Indonesian populations of the silver-lip pearl oyster P. maxima over ~2,000 km, where functional differences had manifested themselves in commercial fitness trait differences (namely growth rate and shell size [118]).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of genetic differences found in the present study would suggest that capelin spawning in different habitats in coastal Newfoundland can be managed as a single stock without risking impact on recruitment or loss of genetic diversity (Carvalho and Hauser 1994). However, studies using loci influenced by divergent selection on high gene-flow species have recently discovered structuring in populations where neutral loci have failed to do so (Michel et al 2010;AndrĂ© et al 2011;Hess et al 2013;Wang et al 2013). Future studies examining the genetic structure of capelin populations associated with differing environmental conditions should therefore scan the genome for outlier loci that are influenced by the environmental variable of interest.…”
Section: Discussionmentioning
confidence: 61%